2017
DOI: 10.3126/ijasbt.v5i4.18771
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Multidrug-Resistant Tuberculosis

Abstract: Multidrug-resistant tuberculosis has been increased worldwide which is a severe problem. A case-control study was carried out among 50 MDR-TB cases and 63 drug susceptible controls to identify risk factors associated with multidrug-resistant tuberculosis (MDR-TB) in Lumbini Zone. Irregularity in taking medicine (OR=2.36), large family size (OR=2.40), farming as occupation (OR=2.83), history of TB and bovine at home (OR=6.5) were statistically associated with MDR-TB. Most of the MDR-TB cases were males (82%) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…This study showed that the odd of MDR-TB was four times greater in households with family size greater than or equal to five. This fact had been confirmed by different literatures in various nations includes Nepal [15,24] and Belarus [25]. According to the previous study, patients with MDR-TB had history of living in crowded house and this created the possible proximity of contact or exposure with infectious source [13].…”
Section: Discussionmentioning
confidence: 66%
“…This study showed that the odd of MDR-TB was four times greater in households with family size greater than or equal to five. This fact had been confirmed by different literatures in various nations includes Nepal [15,24] and Belarus [25]. According to the previous study, patients with MDR-TB had history of living in crowded house and this created the possible proximity of contact or exposure with infectious source [13].…”
Section: Discussionmentioning
confidence: 66%